Compression-bending behaviour of steel-reinforced concrete-filled circular steel tubular columns with preload. (February 2022) - Jia, Zhi-Lu; Shi, Yan-Li; Wang, Wen-Da; Ji, Sun-Hang
Abstract: Due to different construction processes, for steel-reinforced concrete-filled steel tubular (SRCFST) columns, its outer steel tube and inner reinforcing steel can often be used as the vertical support of concrete pouring formwork and floor in the construction process. Therefore, before the whole member is stressed together, steel components may alone or together generate an initial stress, and then affect the mechanical performance of the entire column. In this study, the structural behaviour of circular SRCFST columns with preload effects under coupled compression and bending is analyzed via the verified finite element (FE) model. The influence of different preload ways, namely only preload on the steel tube, and preload on both the steel tube and reinforcing steel, are investigated. Moreover, the relevant factors influencing the performance of SRCFST columns are also studied. The results show that the load versus deflection curves of SRCFST columns with different preload ways are basically identical. In addition, the main parameters affecting the ultimate strength influence coefficient ( k p ) are the preload ratio, the load eccentricity and slenderness ratio. Finally, the compression-bending calculation method considering the influence of the preload effects is proposed to calculate the ultimate strength of circular SRCFST columns with preload effects.